Out of Work and Into School: Labor Market Policies and College Enrollment During the Great Recession - Andrew Barr; Sarah E. Turner (Center for Economic Studies and ifo Institute (CESifo), 2014)
The Great Recession brought large increases in unemployment and college enrollment; we explore how changing labor market conditions affected the decision to enroll, focusing on the role of state-specific dimensions of Unemployment Insurance (UI) policy. We measure the enrollment response to changing economic conditions, comparing eighteen and nineteen year-olds with older individuals likely to have accumulated some labor market experience. We find that individuals in their mid to late-twenties are proportionally more responsive to cyclical variation in economic conditions, and we identify a substantial role of the UI program in determining post-secondary enrollment outcomes. States in which academic post-secondary programs unrelated to a specific occupation are allowable under UI have substantially magnified enrollment responses to local economic conditions. In addition, we provide some of the first evidence that the duration of UI affects a displaced individual's propensity to enroll. These findings identify a substantial overlap between UI policy and post-secondary enrollment decisions, indicating the potential importance of UI in not only providing income but also facilitating investments in skills.
Keywords: I23; J64; J65; I38; H53; 330